Digital Transformation of Business Administration Education in the Era of Artificial Intelligence: : A Conceptual Framework for Higher Education - Eka Annisa Zulqaidah; Kadaruddin Kadaruddin (IJBLE Scientific Publications Community Inc., 2026)
Artificial intelligence (AI) is accelerating the digital transformation of higher education and is changing the competencies expected of Business Administration graduates. This conceptual article develops the Artificial Intelligence-Based Business Administration Learning (AI-BAL) Framework to explain how AI can be integrated into Business Administration curricula without reducing education to technology adoption. The study uses a concept-driven integrative review and theory-synthesis approach. Literature on digital transformation, artificial intelligence in education, AI literacy, management education, human-AI augmentation, and responsible AI was examined and organized through iterative concept identification, categorization, relational mapping, and framework construction. The resulting framework connects four core layers: AI technologies, digital pedagogical transformation, Business Administration competencies, and graduate outcomes. These layers are shaped by external drivers, enabled by institutional leadership, faculty capability, infrastructure, policy, and industry collaboration, and governed by cross-cutting principles of human agency, transparency, fairness, privacy, accountability, inclusion, and academic integrity. The framework positions pedagogy as the mechanism that converts technological affordances into disciplinary competence and proposes a continuous evaluation loop for curriculum improvement. Six propositions specify testable relationships among AI adoption, pedagogy, competency development, institutional readiness, and graduate outcomes. The article contributes a discipline-specific and empirically testable model for curriculum redesign, faculty development, governance, and future research in Business Administration education.